Success in Africa CEO insights from a continent on the rise - Berman, Jonathan E. (Brookline Bibliomotion, Inc, 2013)
In an era of slowing growth, Africa is home to a trillion-dollar, resource-rich economy, and six of the ten fastest growing markets in the world. Success in Africa introduces the ambitious CEOs who are building the continent. These stories of growth, technology, and tradition bring life to one of the most important stories of the global economy: a successful Africa.
Includes bibliographical references and index.
Keywords: Economic development--Africa.